2016
DOI: 10.1111/nmo.12969
|View full text |Cite
|
Sign up to set email alerts
|

Effects of varying dietary content of fermentable short‐chain carbohydrates on symptoms, fecal microenvironment, and cytokine profiles in patients with irritable bowel syndrome

Abstract: Our findings support the efficacy of a LFD in alleviating IBS symptoms, and show changes in inflammatory cytokines, microbiota profile, and SCFAs, which may have consequences for gut health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
184
1
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(200 citation statements)
references
References 41 publications
(64 reference statements)
8
184
1
7
Order By: Relevance
“…The comparator group in one study was a high FODMAP diet42 and in the other was a low FODMAP diet supplemented with fructo-oligosaccharide (fructans) to achieve a ‘normal’ FODMAP intake 48…”
Section: The Low Fodmap Dietmentioning
confidence: 99%
“…The comparator group in one study was a high FODMAP diet42 and in the other was a low FODMAP diet supplemented with fructo-oligosaccharide (fructans) to achieve a ‘normal’ FODMAP intake 48…”
Section: The Low Fodmap Dietmentioning
confidence: 99%
“…The mechanism of benefit is assumed to relate to reduced colonic fermentation25 or greater microbial diversity and reduced total bacterial abundance 26. More specifically, a recent study of 20 patients with diarrhoea-predominant IBS (IBS-D) or IBS-M reported that low FODMAP diet decreased serum levels of proinflammatory interleukin (IL)-6 and IL-8, as well as levels of faecal bacteria (Actinobacteria, Bifidobacterium and Faecalibacterium prausnitzii ), as well as faecal total SCFAs and n-butyric acid compared with baseline 27. Lower levels of Bifidobacteria were confirmed with low FODMAP diet in another study 28.…”
Section: Current Approaches To Manage Visceral Pain In Patients With Ibsmentioning
confidence: 99%
“…For example, in a placebo-controlled crossover feeding study that evaluated 247 gluten-free, casein-free diets in autism, most parents of children could not distinguish the placebo diet from the experimental diet (33) . In this feeding study, all meals and snacks were everyday practice, such as non-adherence (34,35) and the potential for information to be 261 misconstrued on transmission from practitioner to the patient, are replicated in these types of to investigate the impact of the low FODMAP diet on symptoms and immune function (36) .…”
mentioning
confidence: 99%